Business groups and financial decisions in Peru, 1884-1930 - Quiroz N., Alfonso W. (1986)
​The peruvian dominant class has usually been thought of as a sector which inhibited Peru's economic " development and obstructed the process of autonomous industrialization. However, judging from the data gathered by historians and economists, the author conchides that those sectors did have an active entrepreneurial participation in the country's process of economic development. Moreover, between 1884 and 1930, the Peruvian élite not only managed to recover from various crisis using very modern and rational notions of finantial manipulation, but also achieved the diversification of commerce and agriculture, and their integration with finances and manufacture. In short, from the author's point of view, it was the formation of economic investment groups what facilitated the transfer of funds from the export sector to urban investments and the growth of the national market.